Genetic diversity analysis for malting grain traits in barley (Hordeum vulgare) - YADAV, R; JAGSHORAN, JAGSHORAN (The Indian Journal of Agricultural Sciences, 2013)
An expetiment was conducted during 1995-96 and 1996-97 to assess the extent of genetic variation in the set ofbarley (Hordeum vulgare L.) lines comprising both exotic (bred mainly for feed and malt) and indigenous collections(bred mainly for food) through a cluster analysis for 6 malting grain characteristics, viz thin kernel (%), l000-kernelweight, seed shape, germinative energy, water sensitivitiy/tolerance and protein (%). The results indicated the compositionof clusters on the line of their source. Cluster 1 comprises both indigenous and exotic collections with desirabletype of grain characters. One thousand kernel weight showed the significant negative correlation with the of thingrains (%).